2007
DOI: 10.2135/cropsci2006.08.0509
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Quantitative Trait Loci in Rice for Yield, Yield Components, and Agronomic Traits across Years and Locations

Abstract: RESEARCHI dentifying quantitative trait loci (QTLs) associated with economically valuable phenotypes is of particular interest as the basis for developing effi cient strategies for genomics-based approaches to plant improvement. Identifi cation of QTLs is also a valuable starting point for positional cloning of genes underlying quantitative phenotypes and for interpreting the molecular and biochemical mechanisms that condition plant growth and development.The QTL studies that are conducted over several years a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
44
0
3

Year Published

2013
2013
2020
2020

Publication Types

Select...
8
1
1

Relationship

2
8

Authors

Journals

citations
Cited by 68 publications
(59 citation statements)
references
References 63 publications
12
44
0
3
Order By: Relevance
“…Consistent large-effect QTL (qDTY6.1) was observed for grain yield under stress conditions in TPE on chromosome 6 near marker RM2434 with phenotypic variation of 31.3%, 37.9% and 3.6% in DS01, DS02 and FC01 respectively, in these RI lines. The same region was reported to be linked to grain yield 38 , biomass, number of panicles 12 and thousand grain weight 39 in rice. QTL for seedling drought tolerance was reported near RM217 region, and the same region harbours genes expressed early under drought stress 40 and Khowaja et al 41 also reported QTLs for drought avoidance in rice in this region.…”
Section: Qtl Analysismentioning
confidence: 74%
“…Consistent large-effect QTL (qDTY6.1) was observed for grain yield under stress conditions in TPE on chromosome 6 near marker RM2434 with phenotypic variation of 31.3%, 37.9% and 3.6% in DS01, DS02 and FC01 respectively, in these RI lines. The same region was reported to be linked to grain yield 38 , biomass, number of panicles 12 and thousand grain weight 39 in rice. QTL for seedling drought tolerance was reported near RM217 region, and the same region harbours genes expressed early under drought stress 40 and Khowaja et al 41 also reported QTLs for drought avoidance in rice in this region.…”
Section: Qtl Analysismentioning
confidence: 74%
“…Não houve correlação fenotípica entre esses caracteres, ao contrário do que foi observado por Cho et al (2007), que relataram correlação negativa e significativa. Ranawake & Amarasinghe (2014) também relataram correlação negativa, mas não significativa quanto a esses caracteres.…”
Section: Resultsunclassified
“…Genomic DNA was extracted as described in Cho et al (2007) with some modifications. The relative purity and concentration of extracted DNA was estimated using NanoDrop-One (Thermo Scientific).…”
Section: Dna Extraction and Genomic Pcrmentioning
confidence: 99%